A Comparative Analysis of American and Uzbek National Wedding Ceremonies - Rahmonnazarova, Feruzaxon (International Journal on Human-Computing Studies, 2025)
Wedding ceremonies hold a significant place in the cultural traditions of societies around the world. This article provides an in-depth comparative analysis of the traditional wedding ceremonies in America and Uzbekistan, focusing on the differences and similarities in rituals, customs, and symbolic elements. By examining these two distinct cultural practices, we aim to shed light on the diverse ways in which marriage is celebrated and honored, and how these celebrations reflect the values and beliefs of each society.